2001
DOI: 10.1002/hyp.213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of persistent hydrophobic organic compounds in the Columbia River Basin using semipermeable‐membrane devices

Abstract: Abstract:Persistent hydrophobic organic compounds are of concern in the Columbia River because they have been correlated with adverse effects on wildlife. We analysed samples from nine main-stem and six tributary sites throughout the Columbia River Basin (Washington and Oregon) for polychlorinated dibenzo-p-dioxins, dibenzofurans, polychlorinated biphenyls, organochlorine pesticides, and priority-pollutant polycyclic aromatic hydrocarbons. Because these compounds may have important biological consequences at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…These altered flows lead to changes in oxygen supply and oxygen demand and the organic matter content of the shallow hyporheic. As fine sediment encompasses particulate organic matter and material <63 µm, such bed storage also influences nutrient and contaminant transfers within the hyporheic (McCarthy and Gale, 2001;Kronvang et al, 2003). Ecological problems caused by colmation and the smothering of gravel riverbeds by layers of finer sediments include reductions in invertebrate populations, changes to macrophyte communities (Clarke and Wharton, 2001), and the reduced health and reproductive impairment of game fish (Acornley and Sear, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These altered flows lead to changes in oxygen supply and oxygen demand and the organic matter content of the shallow hyporheic. As fine sediment encompasses particulate organic matter and material <63 µm, such bed storage also influences nutrient and contaminant transfers within the hyporheic (McCarthy and Gale, 2001;Kronvang et al, 2003). Ecological problems caused by colmation and the smothering of gravel riverbeds by layers of finer sediments include reductions in invertebrate populations, changes to macrophyte communities (Clarke and Wharton, 2001), and the reduced health and reproductive impairment of game fish (Acornley and Sear, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these contaminants are persistent hydrophobic organic compounds, including polychlorinated biphenyls, polychlorinated dibenzo-p-dioxins, dibenzofurans, polycyclic aromatic compounds and organochlorine (OC) pesticides (McCarthy and Gale 2001). Persistent organic pollutants from these sources typically have high sorption coefficients and tend to partition into the sediment organic matter.…”
mentioning
confidence: 99%
“…1), although sources of dioxins such as pulp mills are located only upstream of these reaches. McCarthy and Gale [37] deployed semi‐permeable membrane devices in the Columbia River and found that some dioxin‐like compounds, DDE, total PCBs, and other contaminants were transferred down the river in the dissolved phase and in association with particulate matter. Fine materials and particulate organic matter deposit primarily in protected peripheral bays such as Baker Bay, Youngs Bay, Cathlamet Bay, and Mott Basin, and in channel bottoms in the mid‐ to upper estuary of the Columbia River (below RK 40; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of large quantities of DDT in orchard crops in the Columbia Basin before 1974 [40] and use of PCBs in electrical transformers, along roads as dust suppressants, or from spills at dam sites could have contributed to the DDE and PCB burdens found in Columbia River biota. Tributaries of the Columbia, such as the Willamette River, also contribute greatly to the contaminant loading [37]. In addition, Thomas and Anthony [31] found the highest concentrations of OC contaminants in great blue heron eggs at a site along the Willamette River.…”
Section: Discussionmentioning
confidence: 99%